Application of fermented product feed to growth performance of fish: A review - Muhamad Dwi Cahya; Yuli Andriani; Kiki Haetami; Risdiana Risdiana (Depik, 2022)
Aquaculture activities cannot be separated from the availability of artificial feed, even 70% of the total production cost is spent on feed, so the availability of good feed, in terms of quality and quantity, is an effort to maintain the success of aquaculture activities. Feeds with high protein have relatively higher prices because some of their raw materials still rely on imports from other countries. The solution to this problem is to use alternative feed ingredients that have good nutritional content, are easy to obtain and do not compete with humans. Organic waste originating from food scraps and agricultural industry residues has considerable potential. However, it is necessary to have a fermentation process as an effort to improve the nutrition and quality of these materials. The purpose of this paper is to determine the extent of utilization of fermented organic waste as fish feed ingredients that can help improve fish growth performance.Keywords:Alternative feed ingredientsFermentationFish feedOrganic waste